Development of Perovskite Manganate-Based Materials as Microwave Absorbers (A Literature Study) - Haiqal, Amanda; Priambodo, Danang Pamungkas; Faddakiri, Fattah Ardhi (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2023)
The 5.0 industrial revolution has led to the rapid development of digital devices and radar detection technology. Electromagnetic (EM) radiation generated by digital devices, such as smartphones, computers, and airplanes, is proven to cause great harm to human health. Manganese perovskite is one material that can produce changes such as its crystal structure, electron transfer, electrical properties, and magnetic properties. Doping applied to manganese perovskite-based materials can induce phenomena such as Colossal Magnetoresistance (CMR) and Magnetocaloric Effect (MCE), giving manganese perovskite-based materials great potential to be used as microwave absorbers. Through this article, the development of various manganese perovskite-based materials as microwave absorbers will be reviewed and summarized. Synthesis methods and microwave absorption mechanisms will also be reviewed. This article focuses on the doping of A-site and B-site manganese perovskite-based materials and their performance in absorbing microwaves. Hopefully, this article can be one of the guidelines for designing new manganese perovskite-based materials, to be applied as microwave absorbers.